Effect of fluoride solution and dentifrice on dental erosion associated or not with abrasion in human enamel: systematic review and metanalysis - Silva, Bruna Machado da (2019)
The evidence of the preventive effect of fluoride in erosion comes from in vitro and in situ/ex vivo studies, but this evidence has been questioned, in relation to its application in the clinic, since no knowledge clinical trial studies. Thus, considering in situ/ex vivo studies approaching clinical trials, this dissertation was composed by two systematic reviews with meta-analyzes to evaluate the efficacy of fluoridated dentifrices (FD) and fluoridated solutions (FS), either monovalent or polyvalent, compared to the negative control group (absence of fluoride) in the prevention and control of enamel erosion, associated or not with abrasion. The secondary objective was to compare the efficacy between FS and FD fluoridated monovalent or polyvalent fluorides. The response variable used in this study was enamel wear, measured by profilometry. This systematic review was registered in the PROSPERO database (CRD42017071118) and followed PRISMA guidelines. A systematic and comprehensive search was performed using PUBMED, WEB OF SCIENCE, SCOPUS, EMBASE, BBO, LILACS, SCIELO and grey literature IBICT-BDTD. A total of 625 studies were obtained and, after exclusion of duplicate articles, only 264 were identified. In both reviews, the selection phase was systematically followed (kappa = 0.98), conducted by two independent authors, who included ten studies on FS and twelve studies on FD for qualitative analysis, and ten studies, for each review, composed the metanalysis. Metanalysis of quantitative analysis showed positive results for polyvalent FS and FD, with a significant effect on the prevention of erosion and erosion/abrasion compared to control group. Monovalent FS were able to prevent only erosion, since no significant difference was observed when evaluating erosion/abrasion compared to the control. In contrast, monovalent FD were able to prevent erosion and erosion/abrasion. When polyvalent and monovalent FS were compared, the first one resulted in less wear after erosive challenge, while the comparison between monovalent and polyvalent FD did not show any significant difference. However, for erosion/abrasion, no significant differences were observed between the FS. Therefore, there is consistent evidence on the preventive effect of FS and FD, especially for the polyvalent vehicles assessed against enamel erosion, associated or not to abrasion.